Malaria case-management under artemether-lumefantrine treatment policy in Uganda - Zurovac, D; Tibenderana, J; Nankabirwa, J; Ssekitooleko, J; Njogu, J; Rwakimari, J; Meek, S; Talisuna, A; Snow, R (BioMed Central, 2008)
Background: Case-management with artemether-lumefantrine (AL) is one of the key strategies to control malaria in many African countries. Yet, the reports on translation of AL implementation activities into clinical practice are scarce. Here the quality of AL case-management is reported from Uganda; approximately one year after AL replaced combination of chloroquine and sulphadoxine-pyrimethamine (CQ+SP) as recommended first line treatment for uncomplicated malaria. Methods: A cross-sectional survey, using a range of quality of care assessment tools, was undertaken at all government and private-not-for-profit facilities in four Ugandan districts. Main outcome measures were AL prescribing, dispensing and counseling practices in comparison with national guidelines, and factors influencing health workers decisions to 1) treat for malaria, and 2) prescribe AL. Results: 195 facilities, 232 health workers and 1,763 outpatient consultations were evaluated. Of 1,200 patients who needed treatement with AL according to guidelines, AL was prescribed for 60%, CQ+SP for 14%, quinine for 4%, CQ for 3%, other antimalarials for 3%, and 16% of patients had no antimalarial drug prescribed. AL was prescribed in the correct dose for 95% of patients. Only three out of seven AL counseling and dispensing tasks were performed for more than 95% of patients. Patients were more likely to be treated for malaria if they presented with main complaint of fever (OR = 5.22; 95% CI: 3.61 - 7.54) and if they were seen by supervised health workers (OR= 1.63; 95% CI: 1.06 - 2.50); however less likely if they were treated by more qualified health workers (OR = 0.61; 95% CI: 0.40 - 0.93) and presented with skin problem (OR = 0.29; 95% CI: 0.15 - 0.55). AL was more likely prescribed if the appropriate weight-specific Al pack was in stock (OR = 6.15; 95% CI: 3.43 - 11.05) and when CQ was absent (OR = 2.16; 95% CI: 1.09 - 4.28). Routine AL implementation activities were not associated with better performance. Conclusion: Although the use of AL was predominant over non-recommended therapies, the quality of AL case-management at the point of care is not yet optimal. There is an urgent need for innovative quality improvement interventions, which should be rigorously tested. Adequate availability of ACTs at the point of care will, however, ultimately determine the success of any performance interventions and ACT policy transitions.